A direct slicing method for optimized lattice structures - Foucault Gilles; Vignat Frederic; Doutre Pierre-Thomas (Mechanics & Industry)
Previous research show that conventional CAD B-Rep methods are highly inefficient to design large lattice structures composed of several thousands of geometric primitives describing struts [2,3]. This paper aims at proposing a method for slicing directly a lattice structure represented as a skeleton: a set of struts connecting nodes, where radius can be constant (cylinder) or linear (cones). The contribution of this method is twofold (1) efficiency: the CAD B-Rep representation is replaced with the skeleton representation which is robust and requires very low resources to be generated. (2) Accuracy: The method generates the explicit and exact geometry of layers with analytic curves, enabling the export into layers with polygons having an arbitrary accuracy.